THE ROLE OF TEACHERS IN IMPROVING DIGITAL-BASED LEARNING MANAGEMENT AT MADRASAH IBTIDAIYAH LEVEL - Divy, Ellen Okta; Lusitania, Nikita; Annur, Saipul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to provide information on the transformation of the role of madrasah ibtidaiyah level teachers in managing learning in the digital era. This research uses the type of literature review research, research that conducts objective assessments, and the data sources are literature books, as well as research journals that are commonly used in research that collects data through literature review. In this study, the literature study method is related to collecting library data, reading and recording and managing writing materials. The type of writing used is a literature study related to the topic or research variability. While the approach in writing uses a qualitative approach with technical content analysis, which is to draw conclusions identifying the specific characteristics of a message objectively and systematically. The research concluded that the role of teachers in the digital age.